Analysis of Instructional Video Developed for Z Generation at Basic Speaking Class - Sri Fatmaning Hartatik; Ike Dian Puspitasari (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
This content analysis was intended to analyze the physical and cognitive designs of a teaching video for Basic Speaking course developed for Z generation at IKIP Budi Utomo Malang. In order to get precise analysis, the researchers involved four English teachers, who teach Basic Speaking, to observe and score the video. To get objective scores, the four teachers were requested to use scoring rubric assessment adapted from (Morain and Swarts, 2012 in Tolentino 2016:109); besides they were also asked to give additional comments on the quality of the video. After the scores and comments were gathered and interpreted, it can be noticed that the video entitled â€œDare to Speak Upâ€ was categorized as a good video. Therefore, those who teach Speaking for beginners are suggested to use this video as one of learning sources. Even though the video was declared to be good, its effectiveness still remained unanswered. Accordingly, further researchers are motivated to do an experimental research to measure the effectiveness of the video.